PERAN PEMERINTAH DAERAH KABUPATEN PURWAKARTA DALAM MENCEGAH, MENANGANI DAN MEMULIHKAN PERMASALAHAN LINGKUNGAN: The Role of the Regional Government of Purwakarta Regency in Preventing, Handling and Restoring Environmental Problems - Tsalsa Fitriyani Zulkarnain; Ninuk Wijiningsih (Faculty of Law, Universitas Trisakti, 2025)
One of the duties of the Purwakarta Regency Regional Government is supervision related to the environmental sector as stated in Law 23 of 2014 concerning Regional Government. Identification problems of this research are: how the implementation of the duties and functions of the Regional Government of Purwakarta Regency in preventing, handling, and restoring environmental problems according to applicable laws and regulations and how the implementation of the duties and functions of the Regional Government of Purwakarta Regency in preventing, handling and restoring environmental problems in the case of industrial waste leakage. The type of research used is normative legal research with secondary data as the main data and primary data in the form of interviews as supporting data. The nature of the research is descriptive, analyzed qualitatively and the conclusion used is deductive The result and conclusion of this research is that PT Indorama Synthetic does not carry out the administrative sanctions given and the Purwakarta Regency Environmental Agency does not supervise the implementation of administrative sanctions.